The Local Wisdom of Dalihan Na Tolu Batak Angkola and the Perspective of al-Ghazali's Moral Thoughts in the Formation of Moral Character - Fata, Nahriyah; Nurdin, Encep Syarif; Hakam, Kama Abdul; Somad, Momod Abdul; Ruyadi, Yadi; Azhar, Mohd. (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2024)
This local wisdom encourages strong social relations within the Toba Batak community, while al-Ghazali's thought emphasizes individual virtues in Islam. This research aimed to understand the contribution of each concept in shaping moral character and moral thinking, as well as exploring the similarities and differences between the two. Apart from that, this research also aims to highlight the relevance and applicability of these two concepts in the context of modern life. This research was used a qualitative approach by analyzing relevant literature about Dalihan Na Tolu's local wisdom and al-Ghazali's moral thoughts. The data was analyzed thematically to identify the two concepts' patterns, similarities, and differences. The research results show that Dalihan Na Tolu local wisdom and al-Ghazali's moral thoughts have significant value in forming moral and moral character. Even though they come from different cultural and religious backgrounds, they can complement each other in enriching their understanding of morality and morals. In addition, this research also highlights the importance of integrating local and universal values in forming of sustainable moral character in modern society. This research underlined the importance of understanding and appreciating cultural and religious values in the formation of moral and moral character. By utilizing the local wisdom of Dalihan Na Tolu and al-Ghazali's moral thoughts, we can develop a holistic and inclusive approach to creating more ethical and harmonious society. Kearifan lokal ini mendorong hubungan sosial yang kuat dalam komunitas Batak Toba, sementara pemikiran al-Ghazali menekankan kebajikan individual dalam Islam. Penelitian ini bertujuan untuk memahami kontribusi masing-masing konsep dalam membentuk karakter moral dan pemikiran akhlak, serta mengeksplorasi kesamaan dan perbedaan di antara keduanya. Selain itu, penelitian ini juga bertujuan untuk menyoroti relevansi dan aplikabilitas kedua konsep ini dalam konteks kehidupan modern. Penelitian ini menggunakan pendekatan kualitatif dengan menganalisis literatur yang relevan tentang kearifan lokal Dalihan Na Tolu dan pemikiran akhlak al-Ghazali. Data dianalisis secara tematik untuk mengidentifikasi pola, kesamaan, dan perbedaan antara kedua konsep tersebut. Hasil penelitian menunjukkan bahwa kearifan lokal Dalihan Na Tolu dan pemikiran akhlak al-Ghazali memiliki nilai yang signifikan dalam pembentukan karakter moral dan akhlak. Meskipun berasal dari latar belakang budaya dan agama yang berbeda, keduanya dapat saling melengkapi dalam memperkaya pemahaman tentang moralitas dan akhlak. Selain itu, penelitian ini juga menyoroti pentingnya integrasi nilai-nilai lokal dan universal dalam pembentukan karakter moral yang berkelanjutan dalam masyarakat modern. Penelitian ini menggarisbawahi pentingnya memahami dan menghargai nilai-nilai budaya dan agama dalam pembentukan karakter moral dan akhlak. Dengan memanfaatkan kearifan lokal Dalihan Na Tolu dan pemikiran akhlak al-Ghazali, kita dapat mengembangkan pendekatan yang holistik dan inklusif dalam menciptakan masyarakat yang lebih beretika dan harmonis.